The Implementation and Outcomes of a Nurse-Run Extracorporeal Membrane Oxygenation Program, a Retrospective Single-Center Study. (15th June 2021) - Odish, Mazen; Yi, Cassia; Tainter, Christopher; Najmaii, Samira; Ovando, Julio; Chechel, Laura; Lipinski, Jerry; Ignatyev, Alex; Pile, Alexander; Yeong Jang, Yun; Lin, Tuo; Tu, Xin M.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Due to a shortage of perfusionists and increasing utilization of extracorporeal membrane oxygenation in the United States, many programs are training nurses as bedside extracorporeal membrane oxygenation specialists (i.e., nurse-run extracorporeal membrane oxygenation). Our objective was to evaluate if a nurse-run extracorporeal membrane oxygenation program has noninferior survival to discharge and complication rates compared with a perfusionist-run extracorporeal membrane oxygenation program. Additionally, to sought to describe increases in extracorporeal membrane oxygenation capacity and the potential for cost savings by implementing a nurse-run extracorporeal membrane oxygenation program.